2020
DOI: 10.1111/jonm.13129
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related behaviours of nurses in Poland: The role of Type D personality

Abstract: Aim: To evaluate the factors affecting the health-related behaviours among nurses in Poland, including the influence of Type D personality. Background: Some nurses appear to adopt an unhealthy lifestyle to cope with the stressful nature of their work, which can affect their professional performance and contribute to the burden on our health care system. However, the factors driving the health-related behaviours among nurses in Poland have not been adequately studied. Method: This was a descriptive study conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
(99 reference statements)
0
3
0
1
Order By: Relevance
“…Significantly higher results were recorded by Stychno et al [27], where 60.6% of nurses had D-type personality. On the other hand, the team of Gieniusz-Wojczyk et al [28], where 1080 nurses working in primary health care and training institutions were examined, personality traits of type D were present in almost half of the surveyed nurses (n=493, 45.6%). People with type D personality have lower self-esteem, establish less social contacts, and have a pessimistic view on reality, which makes taking on challenges more difficult for them [11], they are also more likely to experience chronic stress, and demonstrate predispositions to professional burnout [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly higher results were recorded by Stychno et al [27], where 60.6% of nurses had D-type personality. On the other hand, the team of Gieniusz-Wojczyk et al [28], where 1080 nurses working in primary health care and training institutions were examined, personality traits of type D were present in almost half of the surveyed nurses (n=493, 45.6%). People with type D personality have lower self-esteem, establish less social contacts, and have a pessimistic view on reality, which makes taking on challenges more difficult for them [11], they are also more likely to experience chronic stress, and demonstrate predispositions to professional burnout [12].…”
Section: Discussionmentioning
confidence: 99%
“…Z kolei zespół Gieniusz-Wojczyk i wsp. [28], gdzie przebadano 1080 pielęgniarek pracujących w podstawowej opiece zdrowotnej i placówkach szkoleniowych cechy osobowości typu D były obecne u prawie połowy badanych pielęgniarek (n=493, 45,6%). Osoby z osobowością typu D mają niską samoocenę, zawierają mniej kontaktów społecznych i posiadają pesymistyczne spojrzenie na rzeczywistość, co utrudnia im podejmowanie wyzwań [11], doświadczają one również częściej przewlekłego stresu i mają predyspozycje do wypalenia Empathy and Type D personality as the correlates of level of social skills of primary healthcare nurses zawodowego [12].…”
Section: Dyskusjaunclassified
“…In Germany, in a study conducted in 2010 among the general population, there was a lower prevalence of distressed personality -31%, in Israel in 2011-24.1% (adult volunteers), and in Taiwan in 2013 (general population) -16% [25][26][27]. Studies conducted in Poland, mainly in selected professional groups, have shown that type D personality characterized 27.8% -45.6% of healthcare workers, 30.1% of secondary school teachers, and 43% of students who specialize in dietetics [28][29][30][31]. The frequency of type D in the general population in Poland has been estimated at 9.3% and 34.8%, depending on the study [18,32].…”
Section: Discussionmentioning
confidence: 99%
“…People with a type D personality are characterised by low self-esteem, a pessimistic attitude, chronic stress, a predisposition to burnout and less social contact. All these factors hinder the formation of social skills for such people and cause a sense of social isolation [32,49]. Cho et al [50] reports that the percentage of type D personalities among nurses is higher than in the general population, ranging from 36% to 39%.…”
Section: Discussionmentioning
confidence: 99%